Prophetic Ethics in Kartunmuslimahid Accounts (Study of Muslimah Content) - Rahmawati, Fitri; Alifah, Hidayati; Sofi, Ahmad (Aqwal: Journal of Qur'an and Hadis Studies, 2023)
Prophetic ethics contain commendable values ​​that need to be emulated from the attitude of the Prophet Muhammad. This prophetic ethics comes from the Qur'an. The existence of prophetic ethics really needs to be implemented in everyday life. That Islam has taught us all to have the traits and behaviors exemplified by the Prophet Muhammad. In this writing, it is able to provide insight and understanding of prophetic ethics to other people from cartoonmuslimahid accounts. Prophetic ethics can also be implemented in social media. So that social media users are more careful and can control themselves in posting everything. This writing will discuss the teachings of prophetic ethics in Islam and the application of prophetic ethics in cartoon Muslimahid accounts. This study uses a qualitative method with a type of literature review research. Data collection techniques use observation and documentation, form data using sentences and pictures. The results of this study indicate that there is a prophetic ethics that needs to be emulated from the Prophet Muhammad and this prophetic ethics needs to be applied to oneself, to others in accordance with Islamic teachings and the Qur'an.